Molecular prediction of durable remission after first-line fludarabine-cyclophosphamide-rituximab in chronic lymphocytic leukemia - Rossi, Davide (Blood, 2015)
Fludarabine, cyclophosphamide, and rituximab (FCR) has represented a significant treatment advancement in chronic lymphocytic leukemia (CLL). In the new scenario of targeted agents, there is an increasing interest in identifying patients who gain the maximum benefit from FCR. In this observational multicenter retrospective analysis of 404 CLL patients receiving frontline FCR, the combination of three biomarkers that are widely tested before treatment (IGHV mutation status, 11q deletion and 17p deletion; available in 80% of the study cohort) allowed to identify a very low-risk category of patients carrying mutated IGHV genes but neither 11q or 17p deletion that accounted for 28% of all cases. The majority of very low-risk patients (71%) remained free of progression after treatment and their hazard of relapse decreased after 4 years from FCR. The life expectancy of very low-risk patients (91% at 5 years) was superimposable to that observed in the matched normal general population, indicating that neither the disease nor complications of its treatment affected survival in this favorable CLL group. These findings need a prospective validation and may be helpful for the design of clinical trials aimed at comparing FCR to new targeted treatments of CLL, and, possibly, for optimized disease management.